The performance of artificial intelligence on a national medical licensing examination: the answers of large language models to text questions : research letter: medicine - Geißler, Mark Enrik; Goeben, Merle; Glasmacher, Kira A.; Bereuter, Jean-Paul; Geissler, Rona Berit; Wiest, Isabella; Kolbinger, Fiona R.; Kather, Jakob Nikolas (Deutsches Ärzteblatt, 2024)
Significant advances are being made in the development of large language models (LLM) for use in the field of clinical medicine. LLM are now able to pass major medical exams such as the United States Medical Licensing Examination (USMLE) and two...
Gesehen am 08.04.2025